Offshoring, Firm Selection, and Job Polarisation in General Equilibrium - Hartmut Egger; Kreickemeier Udo; Wrona Jens (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We set up a general equilibrium model, in which offshoring to a low-income country can lead to job polarisation in the high-income country, with the number of jobs paying either very high or very low wages increasing, and jobs in the middle of the wage distribution disappearing. The firm population is heterogenous with respect to firm productivity, and rent sharing leads to a positive link between wages and productivity at the firm level. Offshoring involves fixed and task-specific variable costs, and as a consequence it is chosen only by the most productive firms, and only for those tasks carrying the lowest variable offshoring costs. A reduction in those variable costs increases offshoring at the intensive and at the extensive margin, with domestic employment shifted from the newly offshoring firms in the middle of the productivity distribution to firms at the tails of this distribution, paying either very low or very high wages.
Keywords: F12; F16; F23; 330